Servant leadership: a strategic choice for organisational performance. An empirical discussion from Pakistan. (25th January 2022) - Abbas, Ansar; Saud, Muhammad; Ekowati, Dian; Usman, Indrianawati; Suhariadi, Fendy
Servant leadership style is typically based on positive individual psychology and self-interest. The focus of research today inclines towards the positive psychology of individual leadership styles such as servant leadership. This empirical study ventures on a constructive discussion of the personal inherent desire of servanthood, successful self-management strategies for effective and sustainable performance, and organisational developments in higher education. The natural instinct of serving others' needs first was conceptualised and modelled scientifically for organisational outcomes in the context of Pakistani higher education institutes. Data was obtained through random sampling from public and private sectors. Further, PLS Smart 3.0 was utilised to perform a statistical analysis. Results revealed that servant leadership predicts organisational performance only through two desired outcomes tested hypothetically. Insightful discussion on statistical results, key conclusions practical and theoretical implications have been presented.